Habitat and Macrozoobenthic Diversity in Marine Protected Areas of the Southern Romanian Black Sea Coast - Begun, Tatiana; Teacă, Adrian; Mureşan, Mihaela; Quijón, Pedro A.; Menabit, Selma; Surugiu, Victor (Frontiers in Marine Science, 2022)
Exposure to a variety of anthropogenic stressors has prompted the creation of a growing number of marine protected areas (MPAs). Unfortunately, long-term changes in both the sources of stress and the extent or operation of the MPAs have also occurred, at a pace that is often faster than the research trying to understand the consequences of those changes. This study addresses this challenge by focusing on two MPAs located in the southern Romanian Black Sea, namely the Cape Tuzla and the Mangalia Sulfur springs. Using 95 seafloor samples collected over a 7-year period, we explored distinct benthic habitats and their associated communities in a depth gradient common to both MPAs. We described benthic communities, their density, biomass, and diversity and subsequently used them as indicators of the health of the seafloor. Specifically, we used the M-AMBI*(n) index to assess the ecological status of the benthic habitats found in both MPAs. Our results identified seven distinct habitats across infralittoral and circalittoral areas and described species composition and diversity levels, reaching up to a grand total of 119 benthic taxa. These communities were often dominated by polychaetes and crustaceans in terms of density and by mollusks in terms of biomass. Several mollusks represent key ecosystem engineer species creating or modifying their local habitat conditions. Our results revealed that two thirds of the sampling stations could be characterized as having a good ecological status (GES), and were therefore dominated by species normally considered as either sensitive or indifferent to organic pollution. Meanwhile, the other third of the stations was labeled as non-GES, was dominated by opportunistic species and represent a concern for the coastline system. This study calls for further research to carefully describe the valuable coastal habitats under the frame of MPAs, and to assess the effects of specific pollutants and the response of organisms that seem most affected by these stressors.